Analysis of the stillborn piglet’s distribution in the Large White sows - A. S. Kramarenko; S. S. Kramarenko; S. I. Lugovoy (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2021)
The main aim of this paper was to estimate the piglet stillbirth incidence distribution in the Large White (LW) sows. The population used for the present study is from a pig farm managed by the Limited Liability Company (LLC) “Tavriys’ki svyni” located in Skadovsky district (Kherson region, Ukraine). The experimental materials used for this study consisted of 100 inds. of productive parent sows of the Large White breed. The estimation of reproductive performance was conducted for each animal included in this study. The total number of piglets born (TNB), number of stillborn piglets (NSB) and frequency of stillborn piglets (FSB) per litter were monitored in the first eight parities in the period of eleven years (2007–2017). The 800 farrowings averaged 11.3 piglets per litter. Of the 9037 piglets born, 7895 were live born and 1142 were stillborn. Stillborn pigs were observed in 63.3 ± 1.7 % of the litters and the pig stillbirth incidence was 12.6 ± 0.4 %. The percentage of pigs born dead in total pigs born, obtained in this study is within the range of rates (5 to 15 %) reported for commercial pig farms in other countries. The frequencies of litters with 1, 2, 3, 4 and 5 or more stillborn piglets were 27.1, 14.8, 10.6, 5.8 and 5.0 %, respectively. The frequency of litters with at least one stillborn piglet varied from 44 % (2nd parity) to 76 % (6th parity). Significant factor in the analysis for frequency of litters with at least one stillborn piglet was parity number in sow (Chi-squared test: χ2 = 51.35; df = 7; P < 0.001). This frequency increased as parity number in sow increased (Pearson correlation coefficient: r = 0.929; P < 0.01). We noted that the piglet stillbirth incidence in the LW sow’s litter took place already during the first farrowing for almost half of the sows (46%). In general, this distribution is well approximated by the exponential model equation (y = 73.567*exp(-0.551x); R2 = 97.09 %). The LW sows with stillborn piglets in four out of eight farrowings were the most reported. The value of the entropy of the traits NSB and FSB varied significantly among sows of different parities (Chi-squared test: in both cases P < 0.001). At the same time, a significant increase in the entropy estimates for both traits from the 1st parity to the 8th parity was noted (Spearman's rank correlation: P < 0.001…0.002).